2012
DOI: 10.1080/10412905.2012.646016
|View full text |Cite
|
Sign up to set email alerts
|

The content and composition of the essential oil Found inCarum carviL. commercial fruits obtained from different countries

Abstract: Caraway (Carum carvi L., Apiaceae) is a very popular spice and herb, which is widely applied in the food and pharmaceutical industry. Variations in the essential oil content and composition in twenty commercial caraway samples obtained from retail pharmacies and health shops in different countries were determined using hydrodistillation and capillary GC techniques. The essential oil yields ranged from 0.6% to 5.4%. Eighteen compounds, comprising more than 97% of the composition of oil, were identified in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…The other important compounds extracted usually from hydro/steam distillation include: carvacrol, a-pinene, g-terpinene, linalool, carvenone, and p-cymene. [14][15][16] The fruits of caraway are used extensively as a mild spice and flavoring for culinary purposes in many cuisines. The dried, brown fruits are hard, crescent-shaped achenes, around 2 mm long with five pale ridges.…”
Section: Other Fruits Of Apiaceae Familymentioning
confidence: 99%
“…The other important compounds extracted usually from hydro/steam distillation include: carvacrol, a-pinene, g-terpinene, linalool, carvenone, and p-cymene. [14][15][16] The fruits of caraway are used extensively as a mild spice and flavoring for culinary purposes in many cuisines. The dried, brown fruits are hard, crescent-shaped achenes, around 2 mm long with five pale ridges.…”
Section: Other Fruits Of Apiaceae Familymentioning
confidence: 99%
“…To understand the synergistic toxic effect caused by this botanical pesticide, it is necessary to focus on its active ingredients. The main component of orange peel oil is limonene (87.9-92.5%; Njoroge et al 2009), but caraway oil also contains this cyclic monoterpene (1.5-51.3%; Raal et al 2012). A recent study demonstrated that the ventilation in the migratory locust is adversely affected by limonene in its pure form or as the major component of lovage essential oil (Halawa and Hustert 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Wintergreen oil mainly contains methyl salicylate (97-99.6%; Gurung 2007), which was found to have insecticidal activity against the adzuki bean weevil Callosobruchus chinensis (Park et al 2016). Raal et al (2012) identified carvone (44.5-95.9%) as the main component of Wawrzyniak and Lamparski (2006) found that aqueous extracts of caraway inhibited the feeding activity of the Colorado potato beetle Leptinotarsa decemlineata and its larvae. This suggests that caraway may be responsible for the antifeedant effect found in locusts.…”
Section: Discussionmentioning
confidence: 99%
“…trans-Carveol and b-caryophyllene content in essential oil of caraway usually range from 0 to 0.2% and from 0 to 0.3%, respectively [9] [22], which was similar to what we obtained in the non-stop 135 min HDT (control) treatment (trans-carveol: 0.137% and b-caryophyllene: 0.16%), but the concentrations of transcarveol (0.067 -0.387%) and b-caryophyllene (0.07 -0.237%) were out of range. Collecting oil at each HDT frames can be accounted for trans-carveol and b-caryophyllene for not falling in range previously reported by [9] [22].…”
Section: Discussionmentioning
confidence: 99%
“…Carvone extracted from caraway seed oil is being commercially used to control sprouting of potato tubers during storage . The specific caraway seed essential oil profile depends not only on the variety and the environment , geographical region , and on the age of the plant , but also significantly influenced by the extraction process . Hydrodistillation was reported to modify the profile of crushed coriander seed essential oil , a plant from the same family as caraway.…”
Section: Introductionmentioning
confidence: 99%